Time Pioneers and Travel Behaviour: An Investigation into the Viability of Slow Motion - Sef Baaijens; Peter Nijkamp (Tinbergen Institute, 1997)
This paper positions time in the centre of spatial economic analysis, with a particular view on transport behaviour. The conventional assumption is that there is for most people in our society a constant travel time budget, so that higher speeds tend to lead to longer travel distance. Thisdevelopment is at odds with the notion of sustainable transport, which would require lower levels of mobility. Recently, the scientific construct of a so-called `time pioneer' has been introduced. Such a time pioneer is prepared to give up part of his scarce time for other, as yet unknown purposes. This attitude might generate `slow motion' behaviour.The paper aims to critically review the concept of a time pioneer from a broadperspective on the socio-economic meaning of time in our globalizing society. It investigates the environmental burden of various travel modes against the background of their time consumption.The viability of time pioneering behaviour is next empirically tested by means of an extensive survey among travellers in the Netherlands. Several modelling experiments, such as logit analysis and rough set analysis, are carried out. It is concluded that, while `slow motion' is seemingly an appealing socio-psychological travel mode, the share of time pioneers amongactual travellers is disappointingly low.
Keywords: 330; Verkehr; Zeit; Geschwindigkeitsbegrenzung; Theorie